The Muddle of the 'Westminster Model': A Concept Stretched Beyond Repair. Issue 4 (27th October 2021) - Russell, Meg; Serban, Ruxandra
Abstract: The term 'Westminster model', widely used in both the academic and practitioner literatures, is a familiar one. But detailed examination finds significant confusion about its meaning. This article follows Giovanni Sartori's advice for 'reconstructing' a social science term whose meaning may be unclear through review of its use in the recent literature. It finds that many authors in comparative politics use the term 'Westminster model' without definition, while those providing definitions associate it with a large (and sometimes conflicting) set of attributes, and a set of countries often not demonstrating those attributes. Some have sought to respect this diversity by proposing variants like 'Washminster' or 'Eastminster', while others suggest that the term should be seen as a loose 'family resemblance' concept. But on examination it no longer meets even the – relatively weak – requirements for family resemblance. To end the muddle, and the risk of flawed inferences and false generalization, comparative scholars should drop this term, and select cases based on more precise attributes instead.